Implementation of an Exoskeleton for Neuromuscular Hand Rehabilitation - Troncoso, B.; Alberti Villalobos, Pedro Enrique; Maldonado Cardenas, Patricia Veronica; Peña Jaramillo, Eduardo Ivan; Barría, P. (My University, 2022)
This article shows the design, development, implementation, and control software associated with a hand exoskeleton capable of assisting in basic actions, such as opening and closing. Robotic architectures, geometric and kinematic analysis are reviewed, obtaining a proprietary design based on the biometrics of Chilean individuals. The exoskeleton meets basic clinical requirements, allowing work with ranges of movement in each finger with no pressure points in the skin or discomfort with use, being capable of adjusting to the thumb and adapting to any hand. The software created for training and rehabilitation, both for the therapist and the end-user, contains control of patient records, therapies, and a graphic interface that allows for personalized routines to be configured after calibration. The software allows rehabilitation specialists to be able to use the exoskeleton, after receiving a brief safety and basic function introduction, and thus be able to perform robotic therapies in any health center.
Keywords: exoskeleton; rehabilitation; rehabilitation-techniques; software control